Genetic variation assessment of stacked-trait transgenic maize via conventional breeding - Xujing Wang (BMC Plant Biology, 2019)
Abstract Background The safety assessment and control of stacked transgenic crops is increasingly important due to continuous crop development and is urgently needed in China. The genetic stability of foreign genes and unintended effects are the primary problems encountered in safety assessment. Omics techniques are useful for addressing these problems. The stacked transgenic maize variety 12–5 × IE034, which has insect-resistant and glyphosate-tolerant traits, was developed via a breeding stack using 12–5 and IE034 as parents. Using 12–5 × IE034, its parents (12–5 and IE034), and different maize varieties as materials, we performed proteomic profiling, molecular characterization and a genetic stability analysis. Results Our results showed that the copy number of foreign genes in 12–5 × IE034 is identical to that of its parents 12–5 and IE034. Foreign genes can be stably inherited over different generations. Proteomic profiling analysis found no newly expressed proteins in 12–5 × IE034, and the differences in protein expression between 12 and 5 × IE034 and its parents were within the range of variation of conventional maize varieties. The expression levels of key enzymes participating in the shikimic acid pathway which is related to glyphosate tolerance of 12–5 × IE034 were not significantly different from those of its parents or five conventional maize varieties, which indicated that without selective pressure by glyphosate, the introduced EPSPS synthase is not has a pronounced impact on the synthesis of aromatic amino acids in maize. Conclusions Stacked-trait development via conventional breeding did not have an impact on the genetic stability of T-DNA, and the impact of stacked breeding on the maize proteome was less significant than that of genotypic differences. The results of this study provide a theoretical basis for the development of a safety assessment approach for stacked-trait transgenic crops in China.